ASSESSING THE STUDENTS’ ABILITY IN USING PREPOSITION OF TIME - Imanuel Kamlasi (Jurnal Bebasan, 2018)
The use of preposition of time (at/on/in) still becomes problems for junior high school students. Therefore; it is important to conduct the research on the ability of using preposition of time. This study aims at finding out the students‘ level of ability and describing the problems faced by the students in using preposition of time. The descriptive qualitative method was applied in this research. The instrument was a test. The subject was the second class students of SMP Kristen Kefamenanu. In data analyses, there were four steps; categorizing, tabulating, analyzing and describing. The result showed that the students‘ average score in preposition of time is 67.33 at average level. The highest number of students is at average level and between 60-69 with the total student is twelve. The data showed that the students‘ average score in preposition AT is 66 at average level. The students‘ average score in preposition ON is 68.5 at average level. The students‘ average score in preposition IN is 67.5 at average level. It indicates that the preposition of AT is very difficult for students while preposition ON is more easy for them.